Advanced phosphocreatine-grafted chitosan hydrogel promote wound healing by macrophage modulation - Sheng, Weibei; Qin, Haotian; Wang, Tiehua; Zhao, Jin; Fang, Chongzhou; Zhang, Peng; Liu, Peng; Udduttula, Anjaneyulu; Zeng, Hui; Chen, Yingqi (Frontiers in Bioengineering and Biotechnology, 2023)
The repair of refractory wounds usually caused by trauma or other chronic diseases remained challenging in clinics due to the potential risk of inflammation and inadequate tissue regenerative properties. Among them, the behaviour of immune cells, such as macrophages, is critical in tissue repair. In this study, a water-soluble phosphocreatine-grafted methacryloyl chitosan (CSMP) was synthesized with a one-step lyophilization method, followed by the fabrication of CSMP hydrogel with a photocrosslinked method, which aimed to promote wound healing through macrophage modulation. As a result, the lyophilized CSMP hydrogel had a porous structure with pores ranging in size from 200 to 400 μm, which was larger than the CSM hydrogel's. The lyophilized CSMP hydrogel possessed a higher water absorption rate compared with the CSM hydrogel. The compressive stress and modulus of these hydrogels were increased in the initial 7 days immersion and then gradually decreased during the in vitro immersion in PBS solution up to 21 days; the CSMP hydrogel showed a higher value in these parameters versus the CSM hydrogel. The CSMP hydrogel inhibited the expression of inflammatory factors such as IL-1, IL-6, IL-12, TNF-α, and CCL2 in an in vitro study cocultured with pro-inflammatory factors in pre-treated bone marrow-derived macrophages (BMM). The mRNA sequencing results showed that the CSMP hydrogel might inhibit the macrophages’ M1 type polarization through the NF-Kappa B (NF-κB) signaling pathway. Furthermore, when compared to the control group, the CSMP hydrogel promoted more skin area repair in the mouse wound defect area, and inflammatory factors such as IL-1, IL-6, and TNF-α were lower in the repaired tissue for the CSMP group. Taken together, this phosphate-grafted chitosan hydrogel showed great promise for wound healing through regulating the macrophage’s phenotype via the NF-κB signaling pathway.